Linking work and home life: mediating effects of sleep - Brossoit, Rebecca M., author; Crain, Tori L., advisor; Fisher, Gwenith G., committee member; Ganster, Daniel C., committee member; Rickard, Kathryn M., committee member (Colorado State University. Libraries, 2018)
Recent nationwide polls suggest that work and home are two dominant sources of stress for Americans. There is a vast literature on the relationships between work and home life (e.g., Eby, Casper, Lockwood, Bordeaux, & Brinley, 2005), and theoretical frameworks such as the work-home resources model (Ten Brummelhuis & Bakker, 2012) seek to elucidate the processes between work and home by specifying linking mechanisms. The present study tested the work-home resources model by specifying sleep as a novel personal resource that links work and home life. Specifically, 6-month self-reported and actigraphic sleep quantity and quality were assessed as mediators of the relationships between baseline psychological work demands and work resources (i.e., decision authority and schedule control) and 12-month attitudes and behaviors at home (i.e., relationship satisfaction and spouse-reported relationship strain) in a sample of nurses and certified nursing assistants. The results demonstrate that work demands predicted self-reported sleep quality, but not sleep quantity. Further, work resources predicted self-reported sleep quantity and quality, but sleep quantity and quality did not relate to outcomes at home. Work-related attitudes and behaviors (i.e., job satisfaction, safety compliance, and organizational citizenship behaviors) were also explored; there was some evidence that self-reported sleep quantity and quality predicted job satisfaction and organizational citizenship behaviors, but not safety compliance. Further, self-reported sleep quantity and quality at 6-months explained the relationships between baseline work resources and 12-month job satisfaction.
Keywords: relationship satisfaction; schedule control; work demands; relationship strain; decision authority; sleep